Hedging in Forensic Discourse: A Case Study on Noida Double Murder Interview (International Journal of Linguistics and Indigenous Culture, 2024)
This paper delves into the intricacies of forensic discourse, focusing on linguistic hedging strategies in the context of the Noida Double Murder Case. Positioned at the intersection of linguistics, law, and crime, forensic discourse analysis provides a lens to examine language in legal settings. The paper centres on the 2008 Noida Murder Case, specifically analysing the communication strategies employed by Rajesh and Nupur Talwar during an interview. The paper aims to unravel the linguistic nuances within the interview setting by utilising Taweel et al.’s Hedging Strategi model, grounded by Grice's Cooperative Principle. This paper used a qualitative analysis to decodes linguistic manoeuvres, focusing on hedging strategies. The data were taken from an in-depth interview to obtain empirical information and undergo two stages of analysis identification of conventional maxims and examination of hedging markers and strategies. The analysis reveals intentional deviations from communicative norms, exposing three prominent hedging strategies: Avoidance, Question-to-Question, and Self-Protection. These strategies serve to deflect scrutiny, shape perceptions, and navigate the delicate balance of legal discourse. This paper contributes to forensic linguistics by uncovering the role of hedging strategies in the Noida Double Murder Case. By applying theoretical frameworks to case-specific discourse, the paper enhances our understanding of linguistic dynamics in high-stakes legal interviews, emphasising their significance in navigating complex legal communication.